Energy, exergy, economic and environmental (4E) analysis of serpentine tube absorber photovoltaic thermal system using nano enhanced phase change material - Rajamony, Reji Kumar; Pandey, A. K.; Abd Ghafar, Sofiah Nurhanis; Mohammad Ahmad, Wadaan; Siaw Paw, Johnny Koh; Suraparaju, Subbarama Kousik; Baabbad, Almohannad; Samykano, Mahendran; Paranthaman, Vijayakumar (Elsevier Ltd., 2025)
Photovoltaic thermal systems (PVT) represent an emerging advancement over photovoltaic (PV) modules, offering simultaneous generation of both electricity and heat, but their commercial implementation is limited, and they only function during sunlight. To address the issue, the present research presents an experimental study of PVT systems integrated with surface-modified multi-walled carbon nanotubes enhanced salt hydrate-based phase change material (SMNePCM), considering energy, exergy, economic and environmental viewpoints. Four PVT configurations were tested with varying flow rates from 0.008 to 0.023 kg/s. The results showed a 95 % enhancement in thermal conductivity and 91 % decrement in optical transmittance of the nanocomposite compared to standard salt hydrate PCMs. The PVT-PCM and PVT-SMNePCM systems reduced panel temperatures by 19.8 ◦C and 20.04 ◦C, respectively, increasing electrical efficiency by 32.12 % and 32.0 % compared to conventional PV systems. The overall energy and exergy efficiency of the PVT-SMNePCM systems were 84.18 % and 12.37 %, respectively. The production cost of the hybrid system is Malaysian ringgit (MYR) 0.36 per kWh, significantly lower than the conventional system’s MYR 1.84 per kWh. Additionally, the hybrid system demonstrated superior CO2 mitigation effectiveness. The thermal management of PVT systems using SMNePCM will facilitate the effective commercialization of these systems and enable to operate for nighttime applications.